Exploring the Complexity of Cardiometabolic Risk in Women - Robins, Jo Lynne W. (2011)
Cardiovascular disease (CVD) is the leading cause of death in the United States. Women are more likely than men to present with advanced disease and experience higher CVD-related morbidity and mortality. Metabolic syndrome is a constellation of risk factors for Type 2 diabetes mellitus (T2DM) and CVD. Abdominal adiposity, a component of metabolic syndrome, is associated with insulin resistance and promotes an atherogenic inflammatory milieu. Cardiometabolic risk (CMR) encompasses metabolic syndrome and incorporates other risk factors such as lifestyle choices, gender, and genetics as risk factors for CVD yet still does not include more recently recognized physiological risk factors such as vitamin D deficiency or psychosocial risk factors such as perceived stress and lack of social support. Because a more comprehensive view of CVD risk factors may facilitate earlier identification and risk reduction, we undertook this exploratory pilot study to answer the question, How do healthy women with and without abdominal adiposity differ physiologically and psychosocially?. We recruited a total of 41 women for a single study visit and assessed a battery of baseline physiological and psychological measures. While the women in this study were free of any diagnoses associated with increased CMR, women with increased waist circumference (WC) exhibited significantly altered levels of several measures associated with impending CMR including insulin sensitivity, lipids, and adiponectin as well as lower social support. These findings suggest that a more comprehensive conceptualization of and refinement of measures for CMR may be useful for identifying and reducing CMR and ultimately CVD in women.